Urban environmental education: Principles in action - Alistair Clacherty; Glynis Clacherty (Environmental Association of Southern Africa, 1990)
While the value of environmental education in a natural environment is acknowledged, a case is made for urban environmental education. Principles underlying a programme derived largely from the British Urban Studies movement, in particular, the Art and the Built Environment project (Adams and Ward 1982), are presented as a contribution to urban environmental education in South Africa.